2023
DOI: 10.1186/s13036-023-00338-8
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in modified poly (lactic acid) as tissue engineering materials

Abstract: As an emerging science, tissue engineering and regenerative medicine focus on developing materials to replace, restore or improve organs or tissues and enhancing the cellular capacity to proliferate, migrate and differentiate into different cell types and specific tissues. Renewable resources have been used to develop new materials, resulting in attempts to produce various environmentally friendly biomaterials. Poly (lactic acid) (PLA) is a biopolymer known to be biodegradable and it is produced from the ferme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(4 citation statements)
references
References 195 publications
(194 reference statements)
0
4
0
Order By: Relevance
“… 43 If PLA properties are enhanced with modifications that can be made when mixed with other polymers, the treatment spectrum of diseases with PLA will be enlarged. 44 Indeed, Moghaddam et al claimed that PLA is toxic-free and can be used instead of wet gauze as a breast bolus for surface dose enhancement and dose uniformity improvement during breast intraoperative electron radiotherapy. 3 DeStefano et al showed in their study that PLA can be considered a good choice as a biomedical material and be a contributing biomaterial for the near future.…”
Section: Discussionmentioning
confidence: 99%
“… 43 If PLA properties are enhanced with modifications that can be made when mixed with other polymers, the treatment spectrum of diseases with PLA will be enlarged. 44 Indeed, Moghaddam et al claimed that PLA is toxic-free and can be used instead of wet gauze as a breast bolus for surface dose enhancement and dose uniformity improvement during breast intraoperative electron radiotherapy. 3 DeStefano et al showed in their study that PLA can be considered a good choice as a biomedical material and be a contributing biomaterial for the near future.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, solution viscosity is essential for controlling fiber size and shape. The solution viscosity increment causes an increase in polymer concentration that induces uniform fiber formation with beads [29,70].…”
Section: Morphological and Physical Characterizationmentioning
confidence: 99%
“…However, these polymers have non-reproducible properties from batch to batch and can contain the impurities of endotoxins. Both protein and polysaccharide materials exhibit poor mechanical properties, while polyhydroxyalkanoates exhibit low cell adhesion [ 13 , 14 ] and no osteoconductivity [ 15 , 16 ]. At the same time, the mechanical properties of polyhydroxyalkanoates are better than those of other natural polymers.…”
Section: Introductionmentioning
confidence: 99%